Passing the UKCAT and BMAT Advice, Guidance and Over 650 Questions for Revision and Practice. - Hutton, Rosalie (Student Guides to University Entrance Series., 2015)
The must-have resource to face the UKCAT and BMAT admissions tests with confidence, and succeed in your application to medical or dental school.